Optimization of Engineering Pipe-Line Networks at Hydraulic Calculation - A. Savastsiyonak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
One of the most vital problems in the field of power engineering is a reduction of construction cost. Expenses on construction and operation of engineering networks ensuring functional purpose of buildings. The given paper proposes a methodology for hydraulic calculation of engineering pipeline networks. This methodology allows to reduce cost of the networks up to 5% at the stage of designing while ensuring the same technological parameters and reliability